Implementasi Algoritma Lucifer Untuk Mengamankan Data Inventor Pergudangan - Kasmiran Kasmiran; Pristiwanto Pristiwanto; Siti Nurhabibah Hutagalung (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
Data security is very important in maintaining the confidentiality of information, especially those containing information that is very important and should only be known by certain parties, let alone using delivery via public networks. Cryptography is the science and art of maintaining the confidentiality of data or text by converting it into a form that cannot be recognized anymore, one of the popular algorithms used in solving these problems is the Lucifer algorithm. Cryptography is a way or technique to secure data so that the confidentiality of the data is maintained, so as to avoid attacks by people who are not responsible for the data. This final project realizes a data security software with the Lucifer cryptographic technique algorithm using the Visual Studio 2008 method.